The effect of COVID-19 pandemic government response to top global airline stocks’ performance and risk profile as controlled by market returns - Agustin, Alysson Ace B. (Animo Repository, 2021)
The COVID-19 pandemic affected many lives and industries. What started as an unknown disease on December 31, 2019, became a pandemic on March 11, 2020. The virus is passed onto others when an infected person coughs or sneezes. Because of that, governments worldwide imposed policies to control the spread of the virus. Furthermore, the travel and movement of the people have been limited; hence, one of the most affected industries is the airline industry. This research aims to study the effect of COVID-19 pandemic government response (government stringency index / GSI)to top global airline stocks’ performance (stock mean returns) and risk profile (systematic risk/beta) as controlled by market returns. From the list of FlightGlobal’s (2019) global top airlines based on revenues, 49 airline companies were used in this research. All the gathered data were statistically analyzed using a panel data regression analysis. Using the Hausman test, the researchers determined which panel regression analysis model is appropriate for the data. When the fixed-effects model was not used, the BP-LM test was used to analyze to choose between the random effects model and the pooled OLS model. Following the results of the Hausman test and the BP-LM test, the pooled OLS model was used for stock mean returns, while the fixed-effects model was used for systematic risk. As a result of the research, it has been found that market returns have a positive effect on stock performance, while government response has a negative effect on stock performance. Additionally, market returns have no effect on stock risk profile, while government response has a negative effect on stock risk profile.